2019
DOI: 10.1111/papr.12804
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Exercise‐Induced Hypoalgesia to Repetitive Back Movement in People with Chronic Low Back Pain

Abstract: & AbstractPurpose: To investigate whether people with chronic low back pain (LBP) show dysfunctional exercise-induced hypoalgesia (EIH) in response to repeated contractions of their back muscles during a lifting task. Methods: In this cross-sectional observational study conducted on asymptomatic participants (n = 18) and participants with chronic LBP (n = 21), quantitative sensory testing (QST) was applied extensively over the lumbar region and a remote area before and after a repeated task that involved lifti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…3, Tables 4 and 5). Previous studies have also shown impaired EIH in patients with chronic pain such as WAD [8], chronic musculoskeletal pain [9], knee osteoarthritis [25], chronic low back pain, and fibromyalgia [1][2][3][4]. However, a recent review/focus article concluded that the acute effects of exercise on EIH is variable in chronic pain populations and that not all chronic pain studies demonstrate an impaired EIH [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3, Tables 4 and 5). Previous studies have also shown impaired EIH in patients with chronic pain such as WAD [8], chronic musculoskeletal pain [9], knee osteoarthritis [25], chronic low back pain, and fibromyalgia [1][2][3][4]. However, a recent review/focus article concluded that the acute effects of exercise on EIH is variable in chronic pain populations and that not all chronic pain studies demonstrate an impaired EIH [11].…”
Section: Discussionmentioning
confidence: 99%
“…The medical examination of the neck and upper limbs was meticulous and followed a specific protocol [12]. In summary, the occupational physician performed a physical examination of the neck and upper limbs (shoulders, elbows, wrists, hands, fingers) which included the succeeding steps: [1] inspection, [2] testing for passive and active motion and range, [3] testing for muscle strength, muscle contraction and pain, [4] palpation of joints, muscle tendons, and insertions, [5] bedside neurologic examination, containing sensory exam in hands/fingers assessing different kinds of sensation, including pinprick, light touch (soft brush), and temperature (rolltemp, one roller being cold and the other warm), muscle stretch reflexes (biceps, triceps, brachioradialis, achilles), and [6] The subjects who had been diagnosed with fibromyalgia, traumatically-induced neck pain (whiplash), rheumatic or metabolic disease, neurological disease, had symptoms of joint involvement or tendinitis in the shoulder joint or had a severe mental disorder were excluded from the study.…”
Section: Medical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…CPM and EIH). For instance, a previous study investigating EIH reported a significant within-session PPT change of 29.78 kPa at the low back in healthy controls following a repetitive lifting task [11]. We determined that the lowest MDC gr at the low back was 46.13 kPa.…”
Section: Applicability Of Absolute Reliability In Researchmentioning
confidence: 94%
“…Recently, these paradigms have been increasingly used in research to determine if individuals with chronic pain have an altered pain inhibition response. For example, some studies reported an alteration of pain inhibition in individuals with chronic low back pain (CLBP) using CPM [6][7][8][9] and EIH [10,11].…”
Section: Introductionmentioning
confidence: 99%